Athlete activism and the role of personal and professional positionality: The case of Naomi Osaka - Leppard, T. R. (International Review for the Sociology of Sport, 2022)
In this article I argue that athlete activists' personal and professional positionality influence their activism. Researchers document the powerful impact that athlete activists wield in effecting social change - especially during the civil rights movement. However, the extant literature does not consider the important points of sameness or difference that activists` personal and professional positionality afford them. Athlete activists are not homogenous. Using content analysis, this article examines how Naomi Osaka's leverages her positionality to generate points of sameness and difference with multiple groups. The findings demonstrate that athletes` personal racial identities greatly influence their decision to become an activist and the issues they speak to. Further, their professional positionality is embedded in a history of former activists, current activists, and the racial structure of their sport. I conclude that Osaka is greatly influenced by the points of sameness and difference afforded to her by her multiple personal and professional identities.